Huntington's Disease and Fitness to Stand Trial: The State of Western Australia v Lowick [2016] WASC 339, Fiannaca J. Issue 1 (2nd January 2017) - Freckelton QC, Ian
Abstract : There is an extensive jurisprudence on fitness to stand trial and a substantial clinical literature on Huntington's disease. However, few commentators have given consideration to the circumstances in which the symptomatology of Huntington's disease may result in an accused person being determined unfit to participate in the criminal process. This paper scrutinises the reasoning of the Western Australian Supreme Court in State of Western Australia v Lowick [2016] WASC 339 where such a determination was made and reflects upon the potential for those with Huntington's disease to satisfy the criteria for unfitness, as well as the difficulties which arise in relation to the humane disposition of such persons subsequent to a finding of unfitness. It argues for reform to the law so that such persons can be detained subject to conditions set by a criminal court judge.